A fisiopatologia da obesidade em adultos como fator determinante da gravidade no Covid 19 – uma revisão integrativa da literatura - ROCHA, Bruno Ricardo Pereira (2025)
The objective of the present study is to identify which aspects of the pathophysiology of obesity can trigger the severe form of Covid 19 in adults, interfering in the prevalence, prognosis and mortality rate. This is an integrative systematic review of the literature of an exploratory nature, whose secondary data were extracted from the Lilacs, PubMed and Scielo platforms. DeCS/MESH was used to select the descriptors that were later articulated with the selected Boolean operators, resulting in a general overview of articles that were subjected to the screening process. The inclusion criteria were articles that addressed the severe form of Covid 19 in the context of obesity, with or without comorbidities, whose study population was aged 18 or over, language in Portuguese or English and free, available in full. The exclusion criteria were studies that strayed from the topic, had restrictions outside the age range, were in languages other than English or Portuguese, were only available in the abstract or on a platform with restricted access. To construct the results, the data were summarized in a validated collection instrument, synthesized based on the author's critical analysis, providing a total of 10 articles for the final writing of this integrative review. In the discussion stage of the observed results, all articles correlated obesity as an independent factor for the worsening of covid 19 in adults. The importance of comorbidities and cardiovascular risk factors in creating a harmful metabolic scenario for the patient was also highlighted. Therefore, we conclude that the inflammatory and chronic scenario of obesity is a risk factor for the prevalence, prognosis and mortality of covid 19.